Management: Thesis, Antithesis, Synthesis - Pina e Cunha, Miguel (2019)
Increasingly, managers live in a world of paradox. For instance, they are told that they must manage by surrendering control and that they must stay on top by continuing to learn, thus admitting that they do not fully know what they do. Paradox is becoming increasingly pervasive in and around organizations, increasing the need for an approach to management that allows both researchers and practitioners to address these paradoxes. A synthesis is required between such contradictory forces as efficiency and effectiveness, planning and action, and structure and freedom. A dialectical view of strategy and organizations, built from four identifiable principles of simultaneity, locality, minimality and generality, enables us to build the tools to achieve such synthesis. Put together, these principles offer new perspectives for researchers to look at management phenomena and provide practitioners with a means of addressing the increasingly paradoxical world that they confront.